Three Sides in Search of a Triangle : Singapore-America-India Relations - Asad Latif (Book collections on Project MUSE., 2009)
"Singapore is America's closest security partner in Southeast Asia. The United States has decided to help India become a major world power in the twenty-first century, an objective that is furthered by the nuclear agreement between them. Singapore's relationship with India is an increasingly pertinent feature of Southeast Asia's political and strategic landscape. Whether these three realities, taken together, lay the basis of a triangular relationship among Singapore, America, and India is the question that this book seeks to answer."--Provided by publisher.